Avaliação dos solventes dióxido de carbono supercrítico e propano subcrítico na extração do óleo de girassol - Nimet, Graziane (2009)
The extraction of oil from greasy seeds is traditionally based in the use of organic solvents. Currently the most used method is the process of extraction by n-hexane. Aiming the obtainment of vegetable oil with higher quality using clean technologies with reduction of oil contamination through solvent and minimizing the damage to the environment is that the technology with fluid pressurized has become one alternative viable to extraction. In this context, the current work has the objective to compare the extraction of the oil in sunflower seeds using the carbon dioxide as solvent in supercritical conditions, the propane in subcritical conditions and the n-hexane. At the beginning, the sunflower seeds were characterized, then went by drying process, crush and sifting and, finally through the extraction process. The experiments were led in temperatures of 40, 50, and 60 °C and pressures of 19, 22 e 25 MPa to carbon dioxide, and temperatures of 30, 45 e 60 ºC and pressures of 8, 10, and 12 MPa to propane. It was considered the effect of the temperature and pressure in the reason of the weight the extracted sunflower oil per weight of solvent used to the different experimental conditions, using a factorial planning 22 with 3 repetitions in the central point. The samples of oil extracted were subordinated to quantification analysis of fatty acids, concentrated of vitamin E (α-tocopherol) and stability oxidative. The pie was analyzed as for its protein content. From the experimental data of the extractions kinetics were tasted the Mathematical models of second order and the Sovová. The results showed that extraction with propane subcritical presented higher rate of extraction when compared to carbon dioxide and to n-hexane, indicating that the propane is a solvent more appropriate to extraction of sunflower oil than the carbon dioxide. The sunflower oil obtained in different experimental conditions didn t present alterations as for the content of fatty acids, however, it was noticed difference in the concentration of vitamin E (α-tocopherol). The samples of oils extracted as in supercritical conditions with carbon dioxide as in subcritical conditions using propane presented better oxidative stability, indicated by the induction time of oxidation than the sample extracted with n-hexane. The pies presented protein contents close independent to the solvent used in the extraction of sunflower oil. The Mathematical modeling of second order and the Sovová model were adapted properly to the experimental data of both solvents.